Distortionary tax and general equilibrium analysis of welfare maximized private and public goods consumption (Progressive Agriculture, 2018)
There is a debate on economic efficiency and the improvement of economic welfare. In this research, I have fixed the value of rich and poor with equal weight with an assumption that the consumption tax is the source of government expenditure for public goods. This paper optimized improvement of equality and private consumption share of public goods with the prime revenue of consumption tax. This optimization process has also been analyzed in accordance with the theoretical assumption of Roy`s identity and Marshallian ordinary market demand function for justification of equity and welfare. Finally, this process compared implicitly to the process of Kuznets pattern economic development with taking assumption of distortionary consumption tax to penetrate the relationship between long term economic growth and economic welfare. The empirical evidence found in my earlier publication that consumption tax is welfare augmented in long run if the source of government expenditure is consumption tax to produce public goods. This welfare maximized general equilibrium evidences have potential opportunity of welfare augmented resource mobilization in a developing country where consumption tax is the source of prime revenue.Progressive Agriculture 29 (2): 178-185, 2018